2000
DOI: 10.1016/s0016-7037(00)00449-x
|View full text |Cite
|
Sign up to set email alerts
|

Pb-isotope systematics of a fossil hydrothermal system from the Troodos ophiolite, Cyprus: Evidence for a polyphased alteration history

Abstract: Abstract-Pb-isotopic ratios have been determined on massive sulphides from the Troodos ophiolite and their inferred source rocks: epidosites and greenschist altered dikes. The latter have distinctly higher Pb-isotope ratios than the sulphides. The high 207 Pb/ 204 Pb ratios for the whole rocks indicate the involvement of an old (sedimentary) Pb-component. Extensive leaching of three epidosite samples shows that the radiogenic Pb can be removed and the resulting trend for the leached samples is consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…Pb isotope ratios for the Cypriot massive sulfi des are similar to those of fresh Troodos glasses reported by Rautenschlein et al (1985), and this suggests that the Pb incorporated in the sulfi des is derived from the Troodos basement (Booij et al, 2000), and the above mentioned Pb ratios are primary. Our Pb isotope data are quite similar to those of the Izu-Bonin boninites and Izu-Bonin volcanic front lavas (Figs.…”
Section: Sr Nd and Pb Isotope Ratiossupporting
confidence: 80%
“…Pb isotope ratios for the Cypriot massive sulfi des are similar to those of fresh Troodos glasses reported by Rautenschlein et al (1985), and this suggests that the Pb incorporated in the sulfi des is derived from the Troodos basement (Booij et al, 2000), and the above mentioned Pb ratios are primary. Our Pb isotope data are quite similar to those of the Izu-Bonin boninites and Izu-Bonin volcanic front lavas (Figs.…”
Section: Sr Nd and Pb Isotope Ratiossupporting
confidence: 80%
“…The analyzed metabasites from the Cyclades (metagabbros, metabasalts, and metabasaltic andesites) display a wide range of lead isotope compositions for a relatively small number of samples, especially regarding 207 (Figure 11a,b). Similarly, high whole-rock 207 Pb/ 204 Pb ratios (Figure 11a) have been reported for the hydrothermally altered parts of the Troodos ophiolite complex (greenschists and epidosites) [80]. In the 207 Pb-206 Pb and 208 Pb-206 Pb diagrams, the Cycladic metabasites display a spread beyond the normal MORB field and Troodos glasses [80] and plot within the field of seawater, attesting the effect of seawater alteration on the Cycladic metabasites compositions.…”
Section: Lead Isotope Geochemistrysupporting
confidence: 64%
“…Similarly, high whole-rock 207 Pb/ 204 Pb ratios (Figure 11a) have been reported for the hydrothermally altered parts of the Troodos ophiolite complex (greenschists and epidosites) [80]. In the 207 Pb-206 Pb and 208 Pb-206 Pb diagrams, the Cycladic metabasites display a spread beyond the normal MORB field and Troodos glasses [80] and plot within the field of seawater, attesting the effect of seawater alteration on the Cycladic metabasites compositions. Sample NA-14 (serpentinized harzburgite) has a high 206 Pb/ 204 Pb ratio, probably due to time-integrated development of radiogenic lead caused by a higher U/Pb ratio compared to the other samples (not plotted in Figure 11).…”
Section: Lead Isotope Geochemistrysupporting
confidence: 64%
“…Indeed, Booij et al (2000) showed that sulfides have lower Pb isotope ratios than their source rocks, in this case greenschist samples from the Troodos Ophiolite. The lower isotopic values of some of the pottery samples analyzed in the present study can be interpreted as the result of the presence of sulfides in the clay derived from the greenschist facies gabbros that were used for White Slip II production.…”
Section: Principal Component Analysismentioning
confidence: 99%